2011
DOI: 10.1007/s00335-011-9334-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional evaluation of MITF as a candidate gene for cutaneous melanoma predisposition in pigs

Abstract: Cutaneous melanoma arises from transformed melanocytes and is caused mainly by environmental effects such as ultraviolet radiation and to a lesser extent by predisposing genetic variants. Only a few susceptibility genes for cutaneous melanoma have been identified so far in human; therefore, animal models represent a valuable alternative for genetic studies of this disease. In a previous quantitative trait locus (QTL) study, several susceptibility regions were identified in a swine biomedical model, the MeLiM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…According to ENSEMBL annotation and reported transcript information (Bourneuf et al . ), none of these variants are located in gene coding regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ENSEMBL annotation and reported transcript information (Bourneuf et al . ), none of these variants are located in gene coding regions.…”
Section: Resultsmentioning
confidence: 99%
“…At the EDNRB and MITF selected regions detected by sequencing, the homozygosity dramatically dropped in all five white-spotted breeds, but no such reduction was observed in solid black Laiwu pigs (Fig. 3b) According to ENSEMBL annotation and reported transcript information (Bourneuf et al 2011), none of these variants are located in gene coding regions.…”
Section: Two Candidate Genes For White Spottingmentioning
confidence: 95%
“…The second QTL analysis highlighted a QTL on the swine chromosome 13, directly above MITF locus. However, subsequent studies showed no association between variants in the gene and melanoma phenotypes ( Bourneuf et al, 2011 ). Also, the authors showed that the locus was not amplified in tumor samples, contrary to what is seen in humans.…”
Section: Genetic Susceptibility In the Melim Modelmentioning
confidence: 99%
“…In previous studies, the major predisposition genes for human melanoma were discarded: for example, CDKN2A was excluded thanks to an association and a haplotype analysis [ 21 ]. CDK4 alleles did not segregate with melanoma in a reference population [ 19 ], and lastly an association analysis showed that MITF could not be related to melanoma occurrence in the MeLiM model [ 23 ]. This study used the power of a backcross pedigree to identify 21 genomic regions associated with melanoma occurrence and/or progression phenotypes, ie clinical ulceration and presence of local and/or distant metastasis (superficial lymphadenopathy vs visceral metastasis).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the most significant linkage peak observed in the genome-wide linkage scan was located on SSC13, at about 77Mb according to the version 10.2 of the porcine genome [ 20 ]. The MITF gene was located in this QTL interval, but was discarded as a susceptibility gene, even though its involvement in porcine melanoma tumors makes no doubt [ 23 ]. Although this first attempt to decipher melanoma predisposition in the porcine model yielded interesting results, the experimental design used a low-density marker panel, with an average of one marker every 20cM, thus preventing a fine-mapping of the linked regions.…”
Section: Introductionmentioning
confidence: 99%